2010
DOI: 10.2215/cjn.07641009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Renal Artery and Kidney Abnormalities by Computed Tomography among Healthy Adults

Abstract: Background and objectives: Management of incidental renal artery and kidney abnormalities in patients undergoing computed tomography scans is a clinical challenge because their frequency in healthy subjects has not been precisely estimated. Therefore, the prevalence and management of these abnormalities were determined among a large cohort of potential kidney donors undergoing protocol evaluations.Design, setting, participants, & measurements: All patients at the Mayo Clinic who underwent computed tomographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 41 publications
3
79
3
1
Order By: Relevance
“…Are these patients at increased risk for CKD? Lorenz et al (55) recently found that 11% of potential kidney donors at the Mayo Clinic have at least one kidney stone. Although the finding of a radiographic stone did not lead to exclusion from donation in most (76%), kidney stone was the most common radiographic kidney abnormality and the radiographic kidney abnormality that contributed most to nondonation (39% of exclusions).…”
Section: Asymptomatic Stone Formersmentioning
confidence: 99%
“…Are these patients at increased risk for CKD? Lorenz et al (55) recently found that 11% of potential kidney donors at the Mayo Clinic have at least one kidney stone. Although the finding of a radiographic stone did not lead to exclusion from donation in most (76%), kidney stone was the most common radiographic kidney abnormality and the radiographic kidney abnormality that contributed most to nondonation (39% of exclusions).…”
Section: Asymptomatic Stone Formersmentioning
confidence: 99%
“…CT angiography is a proven tool in this domain. It also has the ability to detect parenchymal abnormalities and calculi; however, its use of ionising radiation is a disadvantage that should be considered when evaluating a donor population [11,12].Balanced steady-state free precession (SSFP) MRA provides a high signal-to-noise ratio (SNR) of blood and a unique T 1 /T 2 weighting [13]. SSFP MRA is a noncontrast technique that has been used for the imaging of renal vasculature in several studies [14][15][16].…”
mentioning
confidence: 99%
“…CT angiography is a proven tool in this domain. It also has the ability to detect parenchymal abnormalities and calculi; however, its use of ionising radiation is a disadvantage that should be considered when evaluating a donor population [11,12].…”
mentioning
confidence: 99%
“…Despite accessory renal arteries 13 and prehilar branching 18 being relatively common, they represented the cause of exclusion in only 2.9% of patients. Multi-disciplinary rounds deemed these patients as requiring more extensive surgical reconstruction, higher operative risks, or necessitating sacrifice of accessory vessels that could compromise graft function.…”
Section: Discussionmentioning
confidence: 99%